Deciphering the multifaceted role of EXO1 in female-related cancers: implications for prognosis and therapeutic responsiveness - Cong Yu; Guoying Wu (Frontiers in Immunology)
BackgroundAberrant function or overactivation of exonuclease 1 (EXO1) may be associated with cancer tumor development, drug resistance, and response to immunotherapy in female-related cancers.MethodsBy analyzing RNA-sequencing data from The Cancer Genome Atlas database, combined with validation through quantitative polymerase chain reaction experiments, we explored the expression levels of EXO1 in breast cancer (BRCA) cell lines and assessed its multidimensional roles in various female-related cancers.ResultsOur experiments revealed elevated expression of EXO1 in BRCA cell lines, consistent with the RNA-sequencing data. The high expression of EXO1 is associated with poor prognosis in various female-related cancers, especially in BRCA and UCEC. It significantly correlates with clinical and pathological characteristics. In specific cancer subtypes like the basal-like subtype of BRCA, high EXO1 expression is associated with a better prognosis. Genetic mutation analysis indicates a higher frequency of EXO1 gene mutations in uterine sarcoma and BRCA. DNA methylation levels may play a role in the regulation of EXO1 gene expression in some cancers. EXO1 expression is correlated with various factors within the tumor immune microenvironment and may be associated with the sensitivity to anticancer drugs.ConclusionEXO1 exhibits multidimensional roles in female-related cancers as a prognostic biomarker and potentially influences tumor immune therapy responses and drug sensitivities. Further studies are needed to fully understand the complex mechanisms underlying these associations and to explore potential therapeutic strategies targeting EXO1.